MANAJEMEN SISTEM PENERIMAAN MURID BARU (SPMB) TERHADAP PENGARUH DATA DAYA TAMPUNG SEKOLAH DI SD NEGERI TEGALSARI KECAMATAN CIKALONGKULON KABUPATEN CIANJUR - Dadang Iskandar; Susilawati; Neng Siti Nuraliah; N. Siti Mariam; R Supyan Sauri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the management of the Student Admission System (SPMB) in relation to the utilization of school capacity data at SD Negeri Tegalsari, Cikalongkulon District, Cianjur Regency, Academic Year 2026/2027. The study employed a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation involving the principal, SPMB committee chairperson, teachers, and school operators. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings revealed that the management of SPMB at SD Negeri Tegalsari was implemented through the management functions of planning, organizing, actuating, and controlling. School capacity determination was based on classroom availability, the number of teachers, educational facilities, and regulations established by the education authority. Capacity data served as the basis for determining student admission quotas, enabling the selection process to be conducted objectively, transparently, and accountably. Challenges encountered during the implementation of SPMB included discrepancies between the number of applicants and available capacity; however, these were addressed through effective coordination among school stakeholders. Therefore, capacity-based SPMB management contributes significantly to the effectiveness of student admissions and supports the maintenance of educational service quality.